Histologic and Immunohistochemical Features Associated with Outcome in Neonatal Necrotizing Enterocolitis - Eaton, Simon; Sebire, Neil; Thyoka, Mandela; Pierro, Agostino (European Journal of Pediatric Surgery, 2014)
Introduction The aim of the study was to compare histopathologic and immunohistochemical markers between survivors and nonsurvivors of surgical necrotizing enterocolitis (NEC).Methods With appropriate ethical approval, archived resection specimens were identified for patients with NEC (Bell Stages II and III) for whom outcome data (survival yes/no) were available. For each specimen, a severely affected part of the bowel and the least affected area, usually the margin, were analyzed. Histologic findings were scored as no necrosis/mucosal necrosis/full-thickness necrosis and immunohistochemistry staining for inflammatory markers vascular cell adhesion protein (VCAM), CD68, CD20, intercellular adhesion molecule (ICAM), human leukocyte antigen (HLA-DR), CD3, Cleaved Caspase-3 (CC3), forkhead box P3 (FOXP3), CD62p, and C4d were performed and scored on a semiquantitative scale (0; no staining to 10, strong extensive staining). All samples were identified by only their study number throughout and the samples were analyzed completely blinded to all clinical information. Data were compared using chi-square test for trend (histologic data) or Mann–Whitney U test.Results A total of 123 slides from 60 patients (birth weight 1.3 ± 0.1kg, gestational age at birth 29.3 ± 0.6 weeks) were examined. Seventy-four specimens (60%) were from survivors and 49 specimens (40%) were from those who subsequently died. There was no relationship between histologic severity of necrosis (none/mucosal/full thickness) and mortality (p = 0.58). VCAM (adhesion molecule; p = 0.005) and CC3 (a marker of apoptosis, p = 0.008) expression was significantly elevated in nonsurvivors, whereas there were no differences in CD68, CD20, ICAM, HLA-DR, CD3, FOXP3, CD62p, or C4d expression.Conclusions There is a poor relationship between histologic severity of bowel necrosis and patient survival in infants undergoing bowel resection for NEC. There is statistically increased expression of VCAM reflecting severity of systemic inflammatory response and evidence of increased apoptosis in the form of CC3 expression in those who subsequently die, but no histologic features can predict outcome.
Keywords: necrotizing enterocolitis; histology; immunohistochemistry; adhesion molecules; caspase